Fiscal consolidation strategy - John F. Cogan; John B. Taylor; Volker Wieland; Maik H. Wolters (Goethe University Frankfurt, Center for Financial Studies (CFS), 2012)
In the aftermath of the global financial crisis and great recession, many countries face substantial deficits and growing debts. In the United States, federal government outlays as a ratio to GDP rose substantially from about 19.5 percent before the crisis to over 24 percent after the crisis. In this paper we consider a fiscal consolidation strategy that brings the budget to balance by gradually reducing this spending ratio over time to the level that prevailed prior to the crisis. A crucial issue is the impact of such a consolidation strategy on the economy. We use structural macroeconomic models to estimate this impact focussing primarily on a dynamic stochastic general equilibrium model with price and wage rigidities and adjustment costs. We separate out the impact of reductions in government purchases and transfers, and we allow for a reduction in both distortionary taxes and government debt relative to the baseline of no consolidation. According to the model simulations GDP rises in the short run upon announcement and implementation of this fiscal consolidation strategy and remains higher than the baseline in the long run. We explore the role of the mix of expenditure cuts and tax reductions as well as gradualism in achieving this policy outcome. Finally, we conduct sensitivity studies regarding the type of model used and its parameterization.
urn:nbn:de:hebis:30:3-272516
Keywords: E27; E62; H62; H63; H68; 330; Fiscal Policy; Fiscal Consolidation; Government Debt; Government Deficit; DSGE Model; Öffentliche Finanzwirtschaft; Öffentliche Schulden; Finanzpolitik; Haushaltskonsolidierung; Theorie